Avaliação, registros de classe e professoras : escutamentos no CIEP Bento Rubião - Fernandes, Ana Cristina Corrêa (2006)
This research if considers to argue the directions of evaluation that teachers of 1º Cycle of Formation are to inscribe, daily, in its practical pedagogical and that they can be express in a specific pertaining to school document: the Registers of Classroom adopted for the City department of Education of the City of Rio De Janeiro in its schools. Search to show equally that they circulate in them you speak written or oralizadas of the teachers potential ambivalences, supporters of the construction of practical instigantes, consonantes avaliativas with a school that if public wants, popular and democratic and of the limits of the pedagogical action when the practical avaliativas if support in sensible of evaluation that resist the dialogue with the multiplicity of citizens that inhabit the classroom despite to the language it has advanced. Thus, searching to understand the ambiguidades that emerge of the daily one, trying to breach with the limits of the directions more good to know the things of the school, the teachers and the evaluation of the children, it wants to contribute for the debate on continued formation of the faculty of the municipal net of education of the River, also reflecting on the challenges found in the proper process of production of the research.